IMPLEMENTASI GAME BINGO PADA METODE DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR TEKS REPORT - MIFTAHUL HIDAYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This Best Practice - based research aims to increase interest in learning and to find out how much improvement is obtained by class IXH students at SMPN 2 Kepanjen Malang in learning report text by implementing bingo games on the discovery learning method . The target of this research is the students of class IXH SMPN 2 Kepanjen Malang Regency, totaling 27 students. Because the genre of text that is at least mastered by students nationally is report text. This is evidenced by the non-achievement of KKM nationally. Likewise with the students of SMPN 2 Kepanjen, the material that students do not master is the report text. However, the SMP English UNBK Question regarding the type of informational report text and how far it is related to the basic competencies being tested will still be analyzed and studied. And the author chooses the game method to answer the problems faced in the field. This game/game application has been specifically designed to assist in the learning process, because it can make students more motivated, able to work with teams in completing missions in the game, enjoy English lessons and be more relaxed and bingo games are considered the most suitable for learning. report text. The results that can be reported from this study are as follows: Students become more active in responding to questions from educators, including the courage of students to ask questions to the teacher and their friends. Learning activities designed according to Discovry Learning syntax require students to be active during the learning process. The class comes alive even though the KBM is at the last hour. There was an increase in learning outcomes as much as 30%. ABSTRAKPenelitian berbasis Best Practice ini bertujuan untuk meningkatkan minat belajar dan untuk mengetahui seberapa besar peningkatan yang di peroleh siswa kelas IXH SMPN 2 Kepanjen Malang dalam pembelajaran teks report dengan mengimplementasikan game bingo pada metode discovery learningDengan meningkatnya minat belajar siswa diharapkan akan meningkat pula hasil belajar siswa .sasaran penelitian ini adalah siswa kelas IXH SMPN 2 Kepanjen Kabupaten Malang yang berjumlah 27 siswa. Karena genre teks yang paling tidak dikuasai oleh siswa secara nasional adalah teks report. Ini dibuktikan tidak tercapainya KKM secara nasional. Begitu juga dengan siswa SMPN 2 Kepanjen, materi yang paling tidak dikuasai oleh siswa adalah teks report. Namun demikian, Soal UNBK Bahasa Inggris SMP terkait jenis teks report informational dan seberapa jauh keterkaitannya dengan kompetensi dasar yang diuji akan tetap dianalisis dan dikaji. Dan penulis memilih metode game untuk menjawab persoalan yang dihadapi di lapangan. Aplikasi permainan/game ini telah dirancang secara khusus untuk membantu dalam proses pembelajaran, karena dapat membuat siswa lebih termotivasi, dapat bekerjasama dengan tim dalam menyelesaikan misi yang ada dalam game, menikmati pelajaran bahasa Inggris dan lebih santai dan game bingo yang dianggap paling sesuai untuk pembelajaran teks report. Hasil yang dapat diilaporkan dari penelitian ini adalah sebagai berikut : Siswa menjadi lebih aktif merespon pertanyaan dari pendidik, termasuk keberanian siswa mengajukan pertanyaan kepada guru maupun temannya. Aktivitas pembelajaran yang dirancang sesuai sintak Discovry Learning mengharuskan peserta didik aktif selama proses pembelajaran. Kelas menjadi hidup sekalipun KBM pada jam terakhir. Terjadi peningkatan hadil belajar sebanyak 30%.